Hypertension – therapeutic approach - Lewandowski, Jacek; Siński, Maciej (Przewodnik Lekarza/Guide for GPs, 2007)
Hypertensive therapy is an effective method of cardiovascular morbidity and mortality reduction. Estimation of blood pressure values and cardiovascular risk stratification should precede initiation of therapy. Therapeutic goals need to be determined before treatment initiation. Cardiovascular risk factors have to be reduced and lifestyle modifications should be initiated in all patients. The majority of patients need combination therapy. The main benefits of antihypertensive treatment are due to lowering of blood pressure per se, and are largely independent of the drugs employed. Target blood pressure in high risk patients should be achieved in a short time. Certain drugs may exert additional, beneficial effects in some groups of patients.